2014
DOI: 10.1007/s11262-014-1132-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased genetic diversity of BVDV-1: recent findings and implications thereof

Abstract: Sequence-based genotyping was recently used to distinguish between the BVDV-1 and BVDV-2 species of the bovine viral diarrhoea virus (BVDV). Quite recently, a new putative species, BVDV-3, was also detected. The phylogenetic analysis of the 5'-untranslated region (UTR) and Npro region has revealed at least 17 distinct subtypes for BVDV-1 to date. The aim of this study was to further investigate the genetic heterogeneity of BVDV-1 in Italy, by analysing 173 virus sequences from isolates collected over an 18-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 21 publications
5
58
0
6
Order By: Relevance
“…Recent studies on the phylogenetics of BVDV in Italy showed a high heterogeneity of subtypes, reporting at least 17 distinct subtypes (Giammarioli et al, 2015). Previous studies (Luzzago et al, 2014) showed that BVDV-1b and 1e had the highest prevalence and a wide spatio-temporal dispersion, conversely to BVDV-1f, characterized by a low prevalence in a restricted area, that is Northern Italy.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies on the phylogenetics of BVDV in Italy showed a high heterogeneity of subtypes, reporting at least 17 distinct subtypes (Giammarioli et al, 2015). Previous studies (Luzzago et al, 2014) showed that BVDV-1b and 1e had the highest prevalence and a wide spatio-temporal dispersion, conversely to BVDV-1f, characterized by a low prevalence in a restricted area, that is Northern Italy.…”
Section: Introductionmentioning
confidence: 97%
“…To date, BVDV is classified into two species, BVDV-1 and BVDV-2, further divided into 20 subtypes of BVDV-1 (1a-1t) (Giammarioli et al, 2015) and three subtypes for BVDV-2 (Beer et al, 2002;Tajima et al, 2001;Vilček et al, 2004). The genome codes for a single polyprotein that is cleaved by both cellular and viral proteases into structural (C, E rns , E1, E2) and non-structural (Npro, p7, NS2-3, NS4A, NS4B, NS5A, NS5B) proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Both are capable of causing acute and persistent infections. Moreover, to the date at least 21 genetic groups of BVDV-1 (named BVDV-1a to BVDV-1r) and four groups in BVDV-2 (BVDV-2a to BVDV-2d) have been described (Alpay & Weşilag, 2015;Deng et al, 2015;Giammarioli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a third BVDV species, called HoBi-like virus or BVDV3, was reported [4]. BVDV-1 is classified by genetic analysis into about 20 subtypes (1a-1t) [5][6][7][8][9][10] and BVDV-2 into three subtypes (2a-2c) [11][12][13]. BVDV subtyping is useful in molecular epidemiological studies, vaccine development and tracing the origin of emerging viruses [14].…”
Section: Introductionmentioning
confidence: 99%